A new species of Rhodania Goux (Hemiptera, Coccoidea, Pseudococcidae) and new records of two other mealybug species from Iran - Williams, D.j.; Moghaddam, M. (Zootaxa, 2007)
Three mealybug species Rhodania aeluropi sp. nov., Spilococcus alhagii (Hall) and Eurycoccus tamariscus Williams are discussed and recorded from Iran for the first time. Rhodania aeluropi was collected on the grass Aleuropus sp. in sugarcane fields, and S. alhagii, a species already known from other countries in the Middle East, is redescribed from specimens collected in Iran. There is considerable variation in the taxonomic characters of S. alhagii in all the material studied.